ECONOMETRIC ANALYSIS OF EXCHANGE RATE IN SERBIA AND ITS INFLUENCE ON AGRICULTURAL SECTOR - Pažun, Brankica; Langović, Zlatko; Langović-Milićević, Ana (Economics of Agriculture, 2016)
This paper attempts to empirically estimate equilibrium exchange rate level of Serbian dinar. In that purpose reduced form equilibrium real exchange rate approach (ERER) is used, developed by IMFs Consultative Group on Exchange Rate Issues (CGER). The research was made by using ARDL approach in the single-country analysis. It has been started from dynamic model which has described relation between real effective exchange rate and a set of fundamental variables. Bound test has been provided due to determination of the long-term relationship existence between variables. F-statistics has been used for long-term relationship testing between dependent variable and set of indicators. Since assumptions were met, least squares method was used for coeffcient estimation. The results have shown constant dinars overvaluation over medium term.